The Role of Diffusion Tensor Imaging in Detecting Microstructural Changes in Prodromal Alzheimer's Disease - Zhang, Bing; Xu, Yun; Zhu, Bin; Kantarci, Kejal (CNS neuroscience & therapeutics, 2014)
Summary The MRI technique diffusion tensor imaging (DTI) is reviewed along with microstructural changes associated with prodromal Alzheimer's disease (AD) as a potential biomarker for clinical applications. The prodromal stage of AD is characterized by mild cognitive impairment (MCI), representing a transitional state between normal aging and AD. Microstructural abnormalities on DTI are promising in vivo biomarkers of gray and white matter changes associated with the progression of AD pathology. Elevated mean diffusivity and decreased fractional anisotropy are consistently found in prodromal AD, and even in cognitively normal elderly who progress to MCI. However, quality of parameter maps may be affected by artifacts of motion, susceptibility, and eddy current‐induced distortions. The DTI maps are typically analyzed by region‐of‐interest or voxel‐based analytic techniques such as tract‐based spatial statistics. DTI‐based index of diffusivity is complementary to macrostructural gray matter changes in the hippocampus in detecting prodromal AD. Breakdown of structural connectivity measured with DTI may impact cognitive performance during early AD. Furthermore, assessment of hippocampal connections may help in understanding the cerebral organization and remodeling associated with treatment response.